The impact of leadership and organizational context on the acceptability of unethical HRM practices - Simões,Eduardo (2020)
Recent research has found that human resource (HR) practitioners judge the acceptability of ethically questionable practices based on the importance their organization attributes to ethical infrastructure (e.g., codes of conduct) and corporate social responsibility practices. This study sought to evaluate the effects of ethical leadership and the aforementioned factors on other non-HR organizational actors. More specifically, this research examined how these individuals judge the acceptability of three ethically dubious HR management practices: discrimination, disregard for the individual, and favoring those in power. Results obtained from data collected through an online survey indicate that ethical leadership is negatively associated with the acceptability of all three practices. Individuals in organizations with a stronger ethical infrastructurealso find discrimination and disregard for the individual less acceptable. The same is true of participants in organizations perceived as more socially responsible regarding employees and economic aspects.